Congenital Adrenal Hyperplasias Presenting in the Newborn and Young Infant - Balsamo, Antonio; Baronio, Federico; Ortolano, Rita; Menabo, Soara; Baldazzi, Lilia; Di Natale, Valeria; Vissani, Sofia; Cassio, Alessandra (Frontiers in Pediatrics, 2020)
Congenital adrenal hyperplasia includes autosomal recessive conditions that affect the adrenal cortex steroidogenic enzymes (cholesterol side-chain cleavage enzyme; 3β-hydroxysteroid dehydrogenase; 17α-hydroxylase/17,20 lyase; P450 oxidoreductase; 21-hydroxylase; and 11β-hydroxylase) and proteins (steroidogenic acute regulatory protein). These are located within the three major pathways of the steroidogenic apparatus involved in the production of mineralocorticoids, glucocorticoids, and androgens. Many countries have introduced newborn screening program (NSP) based on 17-OH-progesterone (17-OHP) immunoassays on dried blood spots, which enable faster diagnosis and treatment of the most severe forms of 21-hydroxylase deficiency (21-OHD). However, in several others, the use of this diagnostic tool has not yet been implemented and clinical diagnosis remains challenging, especially for males. Furthermore, less severe classic forms of 21-OHD and other rarer types of CAHs are not identified by NSP. The aim of this mini review is to highlight both the main clinical characteristics and therapeutic options of these conditions, which may be useful for a differential diagnosis in the neonatal period, while contributing to the biochemical evolution taking place in the steroidogenic field. Currently, chromatographic techniques coupled with tandem mass spectrometry are gaining attention due to an increase in the reliability of the test results of NPS for detecting 21-OHD. Furthermore, the possibility of identifying CAH patients that are not affected by 21-OHD but presenting elevated levels of 17-OHP by NSP and the opportunity to include the recently investigated 11-oxygenated androgens in the steroid profiles are promising tools for a more precise diagnosis and monitoring of some of these conditions.